Immobilization of glucose oxidase And ferrocene redox polymer in cross-linked poly (vinyl alcohol) with bovine serum albumin as protein stabilizer - Jusoh, Norhana; Abdul Aziz, Azila (2006)
A method of tethering a mediator to an enzymatic membrane was studied. Glucose oxidase (GOD) and ferrocene redox polymer were immobilized in cross-linked poly (vinyl alcohol) (CLPVA) with bovine serum albumin (BSA) added as a protein stabilizer. Redox hydrogel polyallylamine ferrocene was prepared by cross-linking polyallylamine hydrochloride with glutaraldehyde and attaching the ferrocene covalently. The biosensor response to glucose was evaluated amperometrically at 0.363V. High BSA concentration resulted in improved current response but lower Kmapp. CLPVA, which had been proven to be an excellent retainer of GOD could not retain both GOD and ferrocene redox polymer effectively, thus affecting the stability of the enzymatic membrane.